Design of a multigenerational energy system with hydrogen production for clean cement plants. (15th June 2023) - Bolt, Andre; Dincer, Ibrahim; Agelin-Chaab, Martin
Abstract: The article aims to provide the design and analysis of a new and unique multigeneration system. This multigeneration system primarily produces methane/natural gas by extracting carbon dioxide from the cement production processes through calcium looping. The hydrogen gas generated in the system was synthesized through polymer electrolyte membrane electrolysis, supported by hydroelectric power. After this, a portion of the hydrogen produced from the system is reacted with carbon dioxide to produce methane. The other useful outputs of the system include electricity, space heating, and domestic hot water. The implemented system design also harnesses other renewable resources, such as solar energy, to enhance other aspects of the design. The system achieved hydrogen and methane production rates of 0.01028 kgs -1 and 0.02045 kgs -1, respectively. Additionally, the system's exergy and energy efficiencies are obtained to be 44.5% and 77.5%, respectively. Furthermore, the energy and exergy heating coefficient of performance values are found to be 1 and 0.5624, respectively.